Early familiarity has fitness consequences for Arctic char ( Salvelinus alpinus) juveniles - Seppä, Teija; Laurila, Anssi; Peuhkuri, Nina; Piironen, Jorma; Lower, Nicola (Canadian Journal of Fisheries and Aquatic Sciences, 2001)
Familiarity is an important factor reducing aggressiveness among individuals. Because of the reduced energy and time expenditure due to lowered aggression, individuals would be expected to perform better in groups of familiar conspecifics as compared with individuals in groups of strangers. However, few studies have examined potential fitness consequences of familiarity. We created familiar (from tanks where several thousands of unrelated fish had been kept since fertilization) and unfamiliar (by combining fish from several tanks) groups of underyearling Arctic char (Salvelinus alpinus) and followed their performance for a 21-day period. Familiarity within groups enhanced survival and body condition of the fish. The fish in familiar groups also grew better in weight and in length. Furthermore, familiar fish differed less in length variation after the experimental period compared with fish reared in unfamiliar groups. There was also a tendency towards similar difference in the variation of weight. These results provide direct evidence for beneficial fitness consequences of early familiarity in Arctic char.